2009
DOI: 10.1111/j.1540-8175.2008.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Left Ventricular Regional Dyssynchrony: Comparison between Real Time 3D Echocardiography and Tissue Doppler Imaging

Abstract: We observed a good correlation between RT3DE and tissue Doppler LV dyssynchrony assessment in patients with advanced heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
0
22
1
1
Order By: Relevance
“…As in our study, EF is frequently used to evaluate the consequences of LVDS in patients with CHF of various degrees. In contrast with the results reported by Vieira et al,1 we found that Tmsv12‐SD% and Tmsv12‐D% yielded results similar to TDI in relation to CHF severity when compared with EF. The selection criteria for CRT take into consideration a LV systolic dysfunction with EF ≤ 35%.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…As in our study, EF is frequently used to evaluate the consequences of LVDS in patients with CHF of various degrees. In contrast with the results reported by Vieira et al,1 we found that Tmsv12‐SD% and Tmsv12‐D% yielded results similar to TDI in relation to CHF severity when compared with EF. The selection criteria for CRT take into consideration a LV systolic dysfunction with EF ≤ 35%.…”
Section: Discussioncontrasting
confidence: 99%
“…RT‐3DE analysis allows simultaneous display of 16 regional volumetric waveforms, enabling temporal comparisons among segments together with LVSD evaluation 17, 18. Vieira et al1 found a good correlation between RT‐3DE and pulsed‐wave TDI LV dyssynchrony assessment in patients with advanced heart failure. This is in agreement with the correlation we found between RT‐3DE and TDI‐Ts12‐SD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34] Assessment of LV dyssynchrony by RT3DE also correlated well with the histogram bandwidth and SD of phase distribution derived from phase analysis and gated myocardial perfusion single photon emission computed tomography (GMPS), an alternative technique in the evaluation of LV dyssynchrony. [31][32][33][34] Assessment of LV dyssynchrony by RT3DE also correlated well with the histogram bandwidth and SD of phase distribution derived from phase analysis and gated myocardial perfusion single photon emission computed tomography (GMPS), an alternative technique in the evaluation of LV dyssynchrony.…”
Section: Validation Of Rt3de Measurements Of LV Dyssynchronymentioning
confidence: 59%
“…12 In addition, 3DE allows evaluation of regional volumes of divided LV segments. However, as described above, the results of PROSPECT trial failed to show apparent benefit of TDI over other conventional echocardiographic measures.…”
Section: Evaluation Of LV Systolic Dyssynchrony By 3de Versus Tdimentioning
confidence: 99%